Examination Of Physical Activity And Body Composıtıon Levels Of Adolescents - Akan Bayrakdar; Özcan Saygın; Yağmur Yıldız (Türk Spor ve Egzersiz Dergisi)
Purpose of the Study: The study aimed to examine adolescents' physical activity and body composition levels according to various variables. Materials and Methods: The participant group of this study consisted of a total of 1104 children (551 girls and 553 boys between the ages of 10-14, enrolled in primary schools in Ankara. In our study, physical activity questionnaire for children (PAQ-C) scale was used to determine the weight, height, BMI measurements, and physical activity level. Result: According to the findings, a significant difference was found in the physical activity levels of boys according to the types of transportation to school (p lt;0.05). When children's sleep duration is examined, boys' and girls' BMI and physical activity levels are similar (p gt;0.05). Significant differences were found in the BMI and physical activity levels of both boys and girls during the daily use of the technological device (p lt;0.05). A negative correlation (p lt;0.05) was found between the daily use of technological devices, sleep duration, and physical activity levels of boys and girls, and a positive correlation with BMI (p lt;0.05). Conclusions: Prolonged screen time is thought to affect body composition and physical activity level negatively. It is thought that the sleeping time should be 8 hours and the screen time should be less in order for BMI and physical activity level to be at appropriate levels.